A method for the non-destructive determination of the knotty core sizes of standing Pinus patula trees, based on ring width assessments at breast height and the pruning history - Munalula, Francis (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScFor (Forest and Wood Science))--University of Stellenbosch, 2010.